Pursuance Étude (Piano), for Ajay Heble - McNeilly, Kevin (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
Kevin McNeilly shares a poem dedicated to Ajay Heble.